Antimicrobial effects of green synthesized silver nanoparticles using Melissa officinalis grown under in vitro condition - Saba Pirtarighat; Maryam Ghannadnia; Saeid Baghshahi (Nanomedicine Journal, 2017)
Objective(s): To evaluate the biosynthesis of Ag NPs using plant extract of Melissa officinalis (at the eight leaf stage) grown under in vitro (controlled) condition for the first time.Materials and Methods: Biosynthesis of Ag NPs using plant extract was carried out and formation of Ag NPs confirmed by UV-Visible spectroscopy, X-ray diffraction (XRD), Field Emission Scanning Electron Microscope (FESEM) and Dynamic Light Scattering (DLS). The functional groups of compounds adsorbed on the Ag NPs were identified using Fourier Transform Infrared Spectroscop (FTIR) studies. The antibacterial activity of the Ag NPs was investigated by agar disc diffusion method.Results: The plant extract showed color change in extract from yellow to brown after formation of Ag NPs. The surface Plasmon resonance found at 450 nm confirmed the formation of Ag NPs. FESEM images revealed relatively spherical- shaped of Ag NPs. The biosynthesized Ag NPs were crystalline in nature with mean diameter about 34.64 nm. FTIR results expounded the functional groups of plant extract responsible for the bio-reduction of silver ions and their interaction between them. The obtained nanoparticles showed good inhibitory activity against the Gram positive and Gram negative bacteria.Conclusion: These results suggested that with changes in plants culture condition it may be possible to obtain nanoparticles with desired characteristics.